2009
DOI: 10.1021/tx900236g
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Metabolism of Estragole in Humans Consuming Fennel Tea

Abstract: The metabolism of the potent carcinogen estragole was investigated in humans after consumption of fennel tea by analyses of its metabolites in blood plasma and urine. Stable isotope dilution assays based on LC-MS/MS detection revealed that 1'-hydroxylation of estragole happened very fast as the concentration of conjugated 1'-hydroxyestragole in urine peaked after 1.5 h, whereas it was no longer detectable after 10 h. Besides the formation of less than 0.41% conjugated 1'-hydroxyestragole of the estragole dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 21 publications
1
50
0
Order By: Relevance
“…The mixture was allowed to stir for 15 min at room temperature and then hydrolyzed with 300 mL ice-cold water. The precipitate was dissolved by adding saturated aqueous NH 4 Cl solution. After separating the organic layer the aqueous solution was extracted with dichloromethane (2 Â 5 mL).…”
Section: Synthesis Of [9-2 H 3 ]-A-terpineol (2)mentioning
confidence: 99%
See 3 more Smart Citations
“…The mixture was allowed to stir for 15 min at room temperature and then hydrolyzed with 300 mL ice-cold water. The precipitate was dissolved by adding saturated aqueous NH 4 Cl solution. After separating the organic layer the aqueous solution was extracted with dichloromethane (2 Â 5 mL).…”
Section: Synthesis Of [9-2 H 3 ]-A-terpineol (2)mentioning
confidence: 99%
“…After separating the organic layer the aqueous solution was extracted with dichloromethane (2 Â 5 mL). The combined organic extracts were washed with water, dried over Na 2 SO 4 and concentrated in a stream of nitrogen. Filtration over Florisil with pentane/diethylether (3/1, v/v) gave pure [9- …”
Section: Synthesis Of [9-2 H 3 ]-A-terpineol (2)mentioning
confidence: 99%
See 2 more Smart Citations
“…Solvent extraction using dichloromethane has been reported for extraction of estragole in Fennel tea followed by GC-MS analysis (Zeller and Rychlik 2006). The effect of using different internal standards on the analytical method performance for estragole has been studied, results have concluded that using p-propyl anisole as an internal standard provided accurate results comparable to those obtained from other methods using stable isotopically labeled internal standard (Zeller et al, 2009). HPLC method using different microextraction procedures have been applied for extraction of estragole and other bioactive compounds from different plant extracts and human urine (Rajabi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%